Corrosion resistant three-dimensional nanotextured silicon for water photo-oxidation. Issue 40 (24th September 2015) - Carter, Rachel; Chatterjee, Shahana; Gordon, Evan; Share, Keith; Erwin, William R.; Cohn, Adam P.; Bardhan, Rizia; Pint, Cary L.
Abstract : Left panel: Effect of corrosion resistance on surface texturing and carbon passivating on silicon and the correlating effect on corrosion rate; Right panel: Photo of water splitting, oxygen gas formation. Abstract : We demonstrate the ability to chemically transform bulk silicon into a nanotextured surface that exhibits excellent electrochemical stability in aqueous conditions for water photo-oxidation. Conformal defective graphene coatings on nanotextured silicon formed by thermal treatment enable over 50× corrosion resistance in aqueous electrolytes based upon Tafel analysis and impedance spectroscopy. This enables nanotextured silicon as an effective oxygen-evolution photoanode for water splitting with saturation current density measured near 35 mA cm −2 under 100 mW cm −2 (1 sun) illumination. Our approach builds upon simple and scalable processing techniques with silicon to develop corrosion resistant electrodes that can benefit a broad range of catalytic and photocatalytic applications.